Animal Welfare: Why is it so Important? - López, Daniela (CIEX JOURNAL, 2018)
This essay presents a brief review about animal welfare as a moral value, containing: An introduction and definition. A description of people or situations that represents the moral value. How we can apply that value in daily life. This essay was written with the purpose to contribute in creating and establish a society that can coexist harmonically with all the living beings.